Early Orthostatic Exercise by Head-Up Tilt With Stepping vs. Standard Care After Severe Traumatic Brain Injury Is Feasible - Riberholt, Christian Gunge; Olsen, Markus Harboe; Søndergaard, Christian Baastrup; Gluud, Christian; Ovesen, Christian; Jakobsen, Janus Christian; Mehlsen, Jesper; Møller, Kirsten (Frontiers in Neurology, 2021)
Background: Intensive rehabilitation of patients after severe traumatic brain injury aims to improve functional outcome. The effect of initiating rehabilitation in the early phase, in the form of head-up mobilization, is unclear. Objective: To assess whether early mobilization is feasible and safe in patients with traumatic brain injury admitted to a neurointensive care unit. Methods: This was a randomized parallel-group clinical trial, including patients with severe traumatic brain injury (Glasgow coma scale < 11 and admission to the neurointensive care unit). The intervention consisted of daily mobilization on a tilt-table for four weeks. The control group received standard care. Outcomes were the number of included participants relative to all patients with traumatic brain injury who were approached for inclusion, the number of conducted mobilization sessions relative to all planned sessions, as well as adverse events and reactions. Information on clinical outcome was collected for exploratory purposes. Results: Thirty-eight participants were included (19 in each group), corresponding to 76% of all approached patients [95% confidence interval (CI) 63% to 86%]. In the intervention group, 74% [95% CI 52% to 89%] of planned sessions were carried out. There was no difference in the number of adverse events, serious adverse events, or adverse reactions between the groups. Conclusions: Early head-up mobilization is feasible in patients with severe traumatic brain injury. Larger randomized clinical trials are needed to explore potential benefits and harms of such an intervention. Trial registration: ClinicalTrials.gov identifier: NCT02924649. Registered on 3rd October 2016